The IMI‐EU H2020 project MOPEAD: Outcome of different screening methods to identify MCI/early AD: Neuropsychiatry and behavioral neurology/Mild cognitive impairment/early symptomatic disease. (7th December 2020) - Winblad, Bengt; Jessen, Frank; Kramberger, Milica G.; Visser, Pieter Jelle; Rodrigo, Adrián; Jamilis, Laura; Rodriguez‐Gomez, Octavio; Sannemann, Lena; Zwan, Marissa D.; Bon, Jaka; Johansson, Gunilla; Nelvig, Anders; et al.
Abstract: Background: The MOPEAD project (Rodríguez‐Gómez O et al, Alzheimers Dement 2019) aims to explore different ways to stimulate early diagnosis of Alzheimer Disease (AD). Four innovative pre‐screening strategies are pursued to identify individuals at high risk for mild cognitive impairment (MCI) or early AD. We aimed to validate positive results from these pre‐screening strategies by performing a full clinical evaluation of the patients at specialized memory clinics. Method: Individuals with a positive pre‐screening result were referred to one of the five participating memory clinics in Ljubljana (Slovenia), Barcelona (Spain), Stockholm (Sweden), Amsterdam (Netherlands), and Cologne (Germany). A harmonized clinical evaluation including physical, neurological, neuropsychological and functionality assessment was performed in these centers as well as MRI neuroimaging and optional cerebral spinal fluid sampling. Based on the result of this evaluation, we estimated the positive predictive value (PPV) of the different pre‐screening strategies, as the proportion of patients with MCI or AD among all referred individuals. Result: A total of 402 individuals with a positive pre‐screening result were evaluated: 91 from a web‐based pre‐screening tool, 161 from an open house initiative, 94 patients from a primary care‐based pre‐screening, and 56 patients identified at diabetes clinics. The number confirmed cases of MCI/AD and PPV were 49(53.8%), 82(50.9%), 58(61.7%), and 47(83.9%) respectively. Within pre‐screening strategy, the results varied greatly between participating countries. Thus, PPV for the web‐based tool was 0% in Germany, and over 70% in Spain and Sweden. Similarly, PPV for the open house initiative was 3% in the Netherlands, but over 95% in Spain. Germany and the Netherlands showed the lowest PPVs (20% and 17% respectively) for the primary care‐based strategy, whereas the all remaining countries had PPVs well over 70%. Country‐specific PPVs estimates in the diabetes clinic strategy were not very reliable due to the small number of patients evaluated. Conclusion: We were able to confirm more than half of patients with a positive result in all four pre‐screening strategies being evaluated. However, our results suggest that despite the harmonization efforts, PPVs of these innovative pre‐screening strategies are highly dependent on the study site.